The Effect of Certification, Competence, and Motivation on Teachers Performance of Country Civil Apparatus in Sawahlunto City - Heryanto, Heryanto; Sumarni, Sri (Archives of Business Research, 2019)
The purpose of this study was to determine the effect of certification and competence on motivation and its impact on the performance of State High School teachers with B Accreditation in Sawahlunto City. This research is motivated by the lack of maximum performance of teachers who have received certification, so this will affect the quality of education in the city of Sawahlunto. The research method uses a quantitative approach with path analysis methods. Respondents of this study were 94 ASN Teachers in State High Schools in Sawahlunto City. The sampling method is total sampling. Hypothesis testing is calculated by IBM Statistical Package for Social Science (SPSS) program version 21.0. The results of this study found that certification has a significant effect on motivation, competence has no significant effect on motivation, certification does not have a significant effect on performance, competence has a significant effect on performance, motivation has a significant effect on performance, indirectly certification through motivation has a significant influence on performance directly competence through motivation has a significant influence on the performance of State High School Teachers in the City of Sawahlunto.